2020
DOI: 10.1016/j.scriptamat.2019.12.010
|View full text |Cite
|
Sign up to set email alerts
|

A criterion for slip transfer at grain boundaries in Al

Abstract: The slip transfer phenomenon was studied at the grain boundaries of pure Aluminum by means of slip trace analysis. Either slip transfer or blocked slip was analyzed in more than 250 grain boundaries and the likelihood of slip transfer between two slip systems across the boundary was assessed. The experimental results indicate that slip transfer was very likely to occur if the residual Burgers vector, ∆b, was below 0.35b and the Luster-Morris parameter was higher than 0.9, and that the ratio of the Luster-Morri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 69 publications
(15 citation statements)
references
References 21 publications
4
11
0
Order By: Relevance
“…if m ≥ 0.75 is chosen as the slip transfer criterion, 92% and 76% of slip transfer and slip blocking events are predicted correctly, respectively. Thus, m > 0.8 seems to be an accurate criterion for slip transfer across regular GB in Ni, similar to the results reported previously for Al [13]. The few experimental data of slip transfer/blocking that do not fulfill this criterion may be attributed to GB with very large twist angle θ, which impedes the slip transfer from one grain to the neighbor but this factor seems to be of second order as compared with the role played by m .…”
Section: Resultssupporting
confidence: 86%
See 2 more Smart Citations
“…if m ≥ 0.75 is chosen as the slip transfer criterion, 92% and 76% of slip transfer and slip blocking events are predicted correctly, respectively. Thus, m > 0.8 seems to be an accurate criterion for slip transfer across regular GB in Ni, similar to the results reported previously for Al [13]. The few experimental data of slip transfer/blocking that do not fulfill this criterion may be attributed to GB with very large twist angle θ, which impedes the slip transfer from one grain to the neighbor but this factor seems to be of second order as compared with the role played by m .…”
Section: Resultssupporting
confidence: 86%
“…Once the two active slip systems across the GB or TB were identified, different metrics can be determined to assess whether they are able to predict slip transfer or blocking. Among them, the Luster-Morris parameter m and the residual Burgers vector ∆b have been used previously [11,13,16,17] in metallic polycrystals. It should be noted that If slip traces were only visible only in one grain across the boundary but not in the other, these GB or TB were not included in the analysis because it was not possible to identify the active slip plane in the latter grain.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…3, the maximum value of m αβ of a 2 slip system with respect to all the BCC slip systems is approximately 0.65. In Alizadeh et al (2020), it was shown that slip systems across grain boundaries can be considered to be aligned if their m αβ ≥ 0.9. Based on this threshold value of 0.9, it can be concluded that the basal a 2 slip system is misaligned with all the BCC slip systems.…”
Section: Colony Microstructure and Lath Interfacesmentioning
confidence: 99%
“…Studies of these deformation modes usually involve the mapping of the 2D microstructure, generally utilizing electron back-scattered diffraction (EBSD), alongside measurements of slip or twinning traces collected using secondary electron images, backscattered electron images, electron channeling contract imaging collected in the scanning electron microscope (SEM), high-resolution digital image correlation (HR-DIC) or atomic force miscroscopy. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] While general trends can be extracted from these combined measurements, they do not enable examination of the origin of deformation events such as slip bands within a given microstructure. For instance, slip traces observed on a specimen's free surface are a projection of a three-dimensional strain localization event that often initiates within the depth of the material.…”
Section: Introductionmentioning
confidence: 99%